Cinnamon free phenolic extract regulates glucose absorption in intestinal cells by inhibiting glucose transporters. (April 2023) - Liu, Yaoyao; Pang, Daorui; Xing, Dongxu; Wang, Weifei; Li, Qian; Liao, Sentai; Li, Erna; Zou, Yuxiao
Abstract: Cinnamon is a traditional herbal medicine that is a valuable source of bioactive phenolic compounds. In this study, we determined the effects of cinnamon free phenolic extract (CFPE) on glucose transport in Caco-2 cells and its possible mechanisms of action. First, the contents of phenolic compounds and flavonoids in bark were compared among four cinnamon cultivars. The 'Taiwan' cultivar had the highest contents of these compounds, and the CFPE was prepared from it. A Caco-2 monolayer was established, and the effect of CFPE on glucose transport across the monolayer was determined. The results showed that CFPE (at 150–300 μg/mL) suppressed glucose transport across the monolayer in a dose-dependent manner. Procyanidin C1, procyanidin B2, procyanidin B1, procyanidin B3, procyanidin A2, and (−)-epicatechin derivatives in CFPE may have contributed to its suppressive effect. Treatment with CFPE decreased the transcript levels of SGK1 encoding serum and glucocorticoid-inducible kinase and PLC/PKC encoding phospholipase C/protein kinase C, which are involved in the signaling pathway associated with glucose transport; and the transcript levels of SGLT1 encoding sodium/glucose cotransporter 1 and GLUT2 encoding glucose transporter 2, the key glucose transporters in this pathway. These findings suggest that CFPE inhibits glucose transport via its effects on the signaling pathway and glucose transporters involved in glucose absorption in intestinal cells. Thus, CFPE has potential applications in preventing postprandial hyperglycemia.